2020
DOI: 10.1002/celc.202000230
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of Hydroxide Ions by Co3O4 and Co3O4@SiO2 Nanoparticles Both at Particle Ensembles and at the Single Particle Level

Abstract: We report that the Co3O4 nanoparticle‐mediated electrochemical oxidation under alkaline conditions of the hydroxide ion on a glassy carbon macroelectrode leads to hydrogen peroxide as the initial oxidation product of electron transfer. The latter is inferred to subsequently partially decompose to dioxygen by catalytic chemical reaction at the nanoparticles. At the single particle level, electrochemical particle‐electrode impacts point out the rate‐determining step and the limiting kinetics of the reaction. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The mentioned peaks that appeared were consistent with Co 3 O 4 (JCPDS No. 01–080-1533, fcc, Fd3m) [37] . A broad peak about 2Θ = 22° is attributed to the amorphous Si [38] .…”
Section: Resultsmentioning
confidence: 99%
“…The mentioned peaks that appeared were consistent with Co 3 O 4 (JCPDS No. 01–080-1533, fcc, Fd3m) [37] . A broad peak about 2Θ = 22° is attributed to the amorphous Si [38] .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the electrochemical behavior of single MOS including IrO x , Fe 2 O 3 , Fe 3 O 4 , CeO 2 , CuO, Co 3 O 4 , TiO 2 , ZnO and CoFe 2 O 4 etc. has been investigated via nano-impact method ( Sardesai et al, 2013 ; Tschulik and Compton, 2014 ; Shimizu et al, 2016a ; Shimizu et al, 2016b ; Zhou et al, 2017 ; Zampardi, et al, 2018 ; Peng et al, 2018 ; Xie et al, 2020 ; Karunathilake et al, 2020 ) The specific research topics mainly involve two aspects: the electrochemical redox behavior and electrocatalysis of single MOS, which is summarized and discussed in the following paragraphs respectively. For a direct type of nano-impact, the nanoparticles are usually fully oxidized (or reduced) so that the electrolysis of the nanoparticles is quantitative.…”
Section: Single Entity Electrochemistry Of Semiconducting Nanoparticlesmentioning
confidence: 99%
“…Some significant applications of the mediated electron transfer for MOS have been reported, examples cover IrO x , Fe 2 O 3 , Co 3 O 4 and CoFe 2 O 4 NPs. ( Zhou et al, 2017 ; Kwon et al, 2010 ; Shimizu et al, 2016a , b ; Xie et al, 2020 ; El Arrassi et al, 2019 ). The initial studies on the mediated impacts of MOS reported the enhanced current transients from the electrocatalysis of individual impacting IrO x NPs toward oxygen evolution reaction (OER).…”
Section: Single Entity Electrochemistry Of Semiconducting Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the most basic level, characterising the behaviour of a single unit in any system, for example, in catalysis, cellular biology, enzyme or reaction kinetics, allows the ensemble response to be better understood and optimised. In the modern era, with advances in electronic components and with a large arsenal of redox systems at the user's disposal, electrochemistry has claimed notable successes in stochastic measurements 1 in the detection of, but not limited to, single nanoparticles, 2 electrocatalysis, 3,4 red blood cells, 5 bacteria 6,7 and viruses. 8 In the world's ocean, calcifying marine phytoplanktoncoccolithophoresplay a crucial role in the global carbon cycle 9 owing to their ability to sequester in excess of 10 15 g of CaCO 3 to the deep ocean per annum.…”
Section: Introductionmentioning
confidence: 99%